Legal Analysis of Self-Preferencing Conducted by Marketplace on Courier Services Based on Anti-Monopoly Law and Unfair Business Competition - Samariadi (Fakultas Hukum Universitas Riau, 2025)
The rapid development of e-commerce has positioned marketplaces as dominant players within the digital economy, while simultaneously giving rise to complex competition issues, one of which is the practice of self-preferencing. This article analyzes the legal implications of self-preferencing practices carried out by marketplaces in Indonesia, particularly the tendency to prioritize or grant exclusive advantages to affiliated or self-owned courier services. Employing a normative legal research method with statutory and conceptual approaches, this study examines the extent to which such practices may violate Law No. 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition (the Anti-Monopoly Law), specifically with regard to abuse of dominant position, discriminatory conduct, and exclusive dealing arrangements. The findings reveal that self-preferencing may hinder fair competition in the courier service sector, disadvantage independent courier providers, restrict consumer choice, and potentially stifle innovation. Such practices create entry barriers for new market entrants and unjustly reinforce marketplace dominance. Accordingly, it is imperative for the Indonesia Competition Commission (KPPU) to proactively monitor and take enforcement actions against self-preferencing practices in order to safeguard a fair and balanced competitive environment in the digital marketplace and promote consumer welfare and market efficiency.